2020
DOI: 10.1016/j.joei.2020.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The potential use of torrefied Nigerian biomass for combustion applications

Abstract: Many countries are seeking to expand their use of solid biomass for electricity and heat generation. Nigeria, too, is exploring its own potential energy crops and indigenous residues. The use of this biomass for energy production is, however, limited by factors such as high moisture content, low bulk and low energy density. This study examines the torrefaction and combustion properties of four readily available Nigerian woody biomass, Gmelina arborea, Terminalia superba, Nauclea diderrichii, Lophira alata and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…However, despite its potential for replacing fossil fuels, direct thermal conversion of biomass via combustion also requires continued insights into reducing or managing the resulting gaseous and particulate emissions as well as ash generation [4]. Whilst chemical and physical properties of biomass can significantly affect its utilisation [5], this paper addresses the role of process design (air staging) on important performance indicators such as temperatures, emissions and fuel consumption rates.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite its potential for replacing fossil fuels, direct thermal conversion of biomass via combustion also requires continued insights into reducing or managing the resulting gaseous and particulate emissions as well as ash generation [4]. Whilst chemical and physical properties of biomass can significantly affect its utilisation [5], this paper addresses the role of process design (air staging) on important performance indicators such as temperatures, emissions and fuel consumption rates.…”
Section: Introductionmentioning
confidence: 99%
“…Tablo 4'de hem oksitleyici (hava) hem de inert (azot) ortamda torrefiye edilen BBA'dan elde edilen biyokömürlerin tutuşma sürelerinin düştüğü yani daha hızlı tutuştukları tespit edilmiştir. Tutuşma süresindeki azalmanın torrefaksiyon sonucu uzaklaşan nem ve biyokütlenin yapısında oluşan değişimlerden kaynaklanmaktadır [48][49].…”
Section: Yakma Işlemi Sonuçlarıunclassified
“…That is notwithstanding other aforementioned agricultural residues, municipal wastes, and industrial wastes which have been reported substantial in quantity in Nigeria [24]. Apart from the studies aimed at assessing biomass energy potential in Nigeria, other authors have focused on experimental characterization of different biomass fuels to facilitate their practical applications in biomass power plants [25], [26], [27]. The legal perspectives on the challenges and prospects of converting organic wastes to electrical energy in Nigeria were the focus of [28], where the authors remarked that a coherent and explicit legal framework is required to promote biomass energy in the country.…”
Section: Introductionmentioning
confidence: 99%